Research through design: developing a visual language for farm soil mapping - Gothe, Jacqueline; Gaul, Chris; Koch, Andrea (InfoDesign, 2021)
The contribution of the information designer and design researcher in an interdisciplinary team is examined through the Developing a Visual Language for Farm Soil Mapping Project. The possibilities of digital information to support soil understanding on specific landholdings is at the forefront of the intention of this information design and visualisation project. This collaboration between designers and design researchers, product developers, soil scientists, agronomists and software developers provides a site of research to chart the participation of the designers and design researchers in the Soil Tech Project 2019-2021. The research through design relationally describes the initial participation by the information design team, the contribution of design and design research to the research and development team and the emergence of insights that have relevance for information design, data visualisation, software development, geography, cartography and directly for digital soil mapping.